Design of microstrip antenna based on different material properties - Ibrahim, Anis Nabihah (2015)
Microstrip antenna has several advantages compared to conventional microwave antenna. These type of antenna are light weight, low volume and thin profile configurations, which can be made conformal. The cost of fabrication is also low and can be manufactured in a large quantities. This project will discuss about the microstrip antenna. The aim of this project is to design a microstrip antenna by using Flame Retardant 4 (FR4) substrate and Roger 4350 substrate which will be operating in Wireless Local Area Network (WLAN). The frequency chosen for the microstrip antenna is 2.4GHz and it has been chosen from IEEE 802.11 which is for the Wireless Fidelity (WiFi) network. This project is divided into three major parts which are calculation, simulation and hardware design. Computer Simulation Technology (CST) microwave studio software used to analyze the radiation pattern of the antenna before fabricated the antenna. Vector Network Analyzer (VNA) used to measure the fabricated antenna to obtain the measurement result. The simulation and measurement results shows a little bit differences for both of the material substrates. Comparison between simulation and measurement result has been made.